2020
DOI: 10.29390/cjrt-2019-018
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal cuff pressures in the PICU: Incidence of underinflation and overinflation

Abstract: Background: While uncuffed endotracheal tubes have been traditionally used in the pediatric intensive care unit (PICU) population, evidence suggests cuffed endotracheal tubes (ETTs) are also safe to use within this population. Nevertheless, risks related to the use of cuffed ETTs increase when guidelines for safe and appropriate use are not followed. The primary goal of this study was to measure the cuff pressure (CP) using a cuff pressure manometer in a group of intubated pediatric subjects and determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…26 Although there remains a paucity of clinical data, an intracuff pressure of 20-30 cm H 2 O sufficiently creates a seal, which reduces risk for microaspiration. 27,28 Complications associated with excessive cuff pressure mirror those reported in the literature for cuffed endotracheal tubes, such as tracheal necrosis, tracheal rupture, and tracheomegaly. 29,30 Pressure exerted by the cuff on the tracheal wall depends on the child's anatomical features and is also affected by positional changes.…”
Section: Cuffed Versus Uncuffed Tracheostomy Tube Usementioning
confidence: 80%
“…26 Although there remains a paucity of clinical data, an intracuff pressure of 20-30 cm H 2 O sufficiently creates a seal, which reduces risk for microaspiration. 27,28 Complications associated with excessive cuff pressure mirror those reported in the literature for cuffed endotracheal tubes, such as tracheal necrosis, tracheal rupture, and tracheomegaly. 29,30 Pressure exerted by the cuff on the tracheal wall depends on the child's anatomical features and is also affected by positional changes.…”
Section: Cuffed Versus Uncuffed Tracheostomy Tube Usementioning
confidence: 80%
“…This is because the intervention of the trachea damages the function of the airway to exclude foreign bodies, causing respiratory secretions to gather above the cuff. When the cuff is underflated, the accumulated secretions above the cuff flows down the gap into the airway, causing aspiration (Parsian et al, 2019; Wettstein et al, 2019). A previously published meta‐analysis (Ying et al, 2016) has found that continuous monitoring of cuff pressure is beneficial to reduce the incidence of aspiration and VAP, which is similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 In a prospective observational study, Wettstein et al found that cuff underinflation is an essential phenomenon in PICU patients. 6 The above fact highlights the importance of standard guidelines for monitoring cuff pressure in critically ill intubated pediatric patients. The various traditional monitoring methods are minimal leak technique, manual palpation of the pilot balloon, bedside manometry, and direct intracuff monitoring.…”
mentioning
confidence: 99%